Doing your master's dissertation from start to finish - Everett, Euris Larry (Sage study skills, 2013)
With examples from real theses, useful action plans in each chapter and a range of practical tips that are often missed in other books, this is a step-by-step guide to help you excel in your Master's dissertation.